2013
DOI: 10.3998/jsais.11880084.0001.104
|View full text |Cite
|
Sign up to set email alerts
|

Online Course Pedagogy and the Constructivist Learning Model

Abstract: The constructivist learning model applies well to the current emphasis in business schools to have more experiential learning. Students construct their own knowledge, guided by their instructors, and learn how to create and extend mental processes for solutions to problems. Another aspect of current college students is that they want to consume everything from education to music to social interaction via information technology on an "any time/any place" basis. Online course pedagogy meets the structural needs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Student interaction is fundamental in establishing social and academic cohesion between students (Perez-Prado & Thirunarayanan, 2002;Rovai & Wighting, 2005;Shea et al, 2014) and the online environment has been touted as a means of promoting constructivist learning (Schell & Janicki, 2013). However this study has highlighted how communication difficulties may act as a barrier to effective interaction.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Student interaction is fundamental in establishing social and academic cohesion between students (Perez-Prado & Thirunarayanan, 2002;Rovai & Wighting, 2005;Shea et al, 2014) and the online environment has been touted as a means of promoting constructivist learning (Schell & Janicki, 2013). However this study has highlighted how communication difficulties may act as a barrier to effective interaction.…”
Section: Resultsmentioning
confidence: 97%
“…It has been suggested that the online environment is an effective platform for promoting constructivist learning as it meets needs for http://dx.doi.org/10.1016/j.chb.2015.05.015 0747-5632/Ó 2015 Elsevier Ltd. All rights reserved. students to access academic coursework at any time while enhancing communication skills (Schell & Janicki, 2013). However constructivism's focus on group activities that facilitate collaborative learning via peer-peer interactions may present challenges for the online learning environment (Huang, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, online learning has evolved from an instructor-centred to a studentcentred paradigm; instructionist and constructivist models underpin these paradigms respectively [10]. This paradigm shift necessitates greater prominence of instructor feedback in providing guideposts, mentoring and coaching learners, and designing assessments which by themselves provide feedback on learning milestones.…”
Section: Introduction and Conceptual Frameworkmentioning
confidence: 99%
“…Researchers have argued that the implementation of constructivist principles has the potential to improve the efficiency and effectiveness of teaching and learning (Pratton & Hales, 1986;Santmire, Giraud, & Grosskopf, 1999) and to prepare lifelong learners (Huang, 2002). Constructivist model of teaching on the college level would be more effective than the traditional approach, where the students would be more actively involved in the learning processes (Schell & Janicki, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The widespread use of technologies for educational purposes among university students and faculty members requires pedagogical and instructional changes and support (Gilakjani et al, 2013). The principles of constructivism have been recommended as appropriate for shaping teaching and learning processes in educational environments that use ICTs (Oliver, 2002;Bailey & Card, 2009;Schell& Janicki 2013;Gilakjani et al, 2013).…”
Section: Introductionmentioning
confidence: 99%